ROLES OF DZONGPON IN MONYUL REGION OF ARUNACHAL PRADESH - Sangey, Phurpa (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Mon region which includes modern-day Tawang and West Kameng, has a similar culture and adheres to Tibetan Buddhism. Only in 1951 did Indian Army official Major Bob Khating stop tax collection among the Monpas. Prior to 1951, Tibetan officials known as dzongpon used to collect various types of taxes from the region. Under the Dzongpon system, monks were appointed as Dzongpons to run the administration based on their managerial ability and strong administrative acumen. The Dzongpon were the Dzong’s highest administrative authority, appointed by the appropriate authority from Tibet’s monasteries. These dzongpons were in charge of collecting various types of taxes in the form of grain and other important edible items. The tax collected in the region was used in the monastery, and a portion of the tax was imported to Lhasa. Aside from Tawang, the Tibetans built two more dzongs at Dirang and Khalegteng (present-day west kameng) to collect taxes from the Monpas. The main idea of this paper is to discuss the roles and functions of Dzongpons in Monyul region. There were four dzongs in Monyul during Dzongpon period i.e. Gyang Khar Dzong, Senge Dzong, Dirang Dzong and Taklung Dzong. Except Senge Dzong each dzongpon has its own administrative unit and were appointed mostly from Tsona Dzong. This paper also explains why dzongpons were able to hold power over the Monyul region despite the signing of Mac Mohan line in the year 1914 between the representative of Tibet, British India and China.